The Correlation of Students’ Mental Health and English Learning Achievement - Hasriati Nur (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The main objective of this research was to find out whether or not there is a correlation between students’ Mental Health and students’ Learning English achievement at SMAN 3 Bone. This research used a correlational approach. The population in this research was the tenth-grade students’ of SMAN 3 Bone, consisting of 12 class with a total of 439 students and random sampling was used to select sample of the research. The data in this research taken by using questionnaire in application and test. The data from questionnaire aimed to know the mental health of the students, while the data from test was intended to find out the students’ English achievement. The findings of the research showed that the correlation between students’ Mental Health and students’ English Achievement was -0.771, meaning that there was a significant or enough correlation between students’ Mental Health and students’ English achievement on the tenth-grade students at SMAN 3 Bone. This implies that the higher the mental health, the lower the English achievement, and vice versa.Keywords: Correlational Research, English Achievement, Mental Health.